2022
DOI: 10.3389/fnut.2022.981511
|View full text |Cite
|
Sign up to set email alerts
|

Altered mannose metabolism in chronic stress and depression is rapidly reversed by vitamin B12

Abstract: GDP-Mannose Pyrophosphorylase B (GMPPB) is a key enzyme for glycosylation. Previous studies suggested a dysregulation of GMPBB and mannose in depression. Evidence, however, was sporadic and interventions to reverse these changes are unknown. Here, we show that GMPPB protein, but not RNA abundance is increased in the postmortem prefrontal cortex (PFC) of depressed patients and the chronic variable stress (CVS) mouse-model. This is accompanied by higher plasma mannose levels. Importantly, a single dose of intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To support ACSS2 as a potential therapeutic target, D-mannose was specifically selected as a rapid ACSS2 inducer to mediate fast- and long-acting antidepressant responses. The findings of a previous report support that D-mannose metabolism dysfunction is closely involved in depression patients or mice with depressive-like behaviors and that vitamin B12 can rapidly normalize mannose metabolism to improve chronic stress induced depressive-like behaviors of mice [ 43 ]. Unexpectedly, here, we found that a single gavage of 200 μl 20% D-mannose produced significant reductions in depressive symptoms.…”
Section: Discussionmentioning
confidence: 53%
“…To support ACSS2 as a potential therapeutic target, D-mannose was specifically selected as a rapid ACSS2 inducer to mediate fast- and long-acting antidepressant responses. The findings of a previous report support that D-mannose metabolism dysfunction is closely involved in depression patients or mice with depressive-like behaviors and that vitamin B12 can rapidly normalize mannose metabolism to improve chronic stress induced depressive-like behaviors of mice [ 43 ]. Unexpectedly, here, we found that a single gavage of 200 μl 20% D-mannose produced significant reductions in depressive symptoms.…”
Section: Discussionmentioning
confidence: 53%
“…Pregnant mother mice or pups were sacrificed and brain as well as skeletal muscle tissue ( musculus quadriceps femoris ) from embryos or pups was isolated. Tissue lysates were prepared as described previously ( Franzka et al, 2022 ). Shortly, samples were homogenized with the Potter S tissue homogenizer (Sartorius) in RIPA buffer [50 mM Tris-HCl pH 7.4, 150 mM NaCl, 1% (v/v) NP-40, 1% (w/v) sodium deoxycholate, 0.1% (w/v) SDS, 1 mM EDTA] and complete protease inhibitor (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research in our team demonstrated that a single acute dose of vitamin B12 reduced depressive-like behaviors in mice in the chronic mild stress (CMS)-model 14 . Additionally, vitamin B12 rescued stress-induced alterations in plasma mannose and Gmppb 15 , a key enzyme of glycosylation metabolism associated with depression 16 . Despite these correlative findings, it is unclear how vitamin B12 mediates stress resilience and improves markers of depression on a molecular level.…”
Section: Introductionmentioning
confidence: 97%